Polo-like kinase 2 phosphorylation of amyloid precursor protein regulates activity-dependent amyloidogenic processing. (1st May 2017) - Lee, Yeunkum; Lee, Ji Soo; Lee, Kea Joo; Turner, R. Scott; Hoe, Hyang-Sook; Pak, Daniel T.S.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder with cognitive deficits. Amyloidogenic processing of amyloid precursor protein (APP) produces amyloid β (Aβ), the major component of hallmark AD plaques. Synaptic activity stimulates APP cleavage, whereas APP promotes excitatory synaptic transmission, suggesting APP participates in neuronal homeostasis. However, mechanisms linking synaptic activity to APP processing are unclear. Here we show that Polo-like kinase 2 (Plk2), an activity-inducible regulator of homeostatic plasticity, directly binds and phosphorylates threonine-668 and serine-675 of APP in vitro and associates with APP in vivo . Plk2 accelerates APP amyloidogenic cleavage by β-secretase at synapses and is required for neuronal overactivity-stimulated Aβ secretion. These findings implicate Plk2 as a novel mediator of activity-dependent APP amyloidogenic processing. Graphical abstract: Highlights: Only N-terminal antibodies recognize postsynaptic pools of APP in cultured neurons. Plk2 is required for activity-dependent β-site processing of synaptic APP. Plk2 interacts directly with and phosphorylates APP at Ser675 and Thr688. APP dual phosphorylation by Plk2 regulates its surface expression and β-processing.